2015 4th International Conference on Advanced Logistics and Transport (ICALT) 2015
DOI: 10.1109/icadlt.2015.7136630
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics for logistics and transportation

Abstract: Nowadays, there are many challenges for the logistics industry mainly with the integration of E-commerce and new sources of data such as smartphones, sensors, GPS and other devices. Those new data sources generate daily a huge quantity of unstructured data, to deal with such complex data, the use of big data analytic tools becomes an obligation.In this context, many works have been done recently in the integration of big data analytics in the logistics industry. In this paper, we propose to give a review of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In the last years, Big Data analytic approaches are becoming more popular in a wide variety of industries and purposes such for medicine [20][21], social networks recommendations [22], logistic [23], structural health monitoring [24] [25], business strategy development [26] or power consumption in manufacturing [27]. For the wind energy industry, some studies have been also identified where a business intelligence approach is presented for failure prognosis [28] or the requirements for a Big Data approach are analyzed [29].…”
Section: State Of Artmentioning
confidence: 99%
“…In the last years, Big Data analytic approaches are becoming more popular in a wide variety of industries and purposes such for medicine [20][21], social networks recommendations [22], logistic [23], structural health monitoring [24] [25], business strategy development [26] or power consumption in manufacturing [27]. For the wind energy industry, some studies have been also identified where a business intelligence approach is presented for failure prognosis [28] or the requirements for a Big Data approach are analyzed [29].…”
Section: State Of Artmentioning
confidence: 99%
“…The data are collected from a very large network of sensors and devices. Big data analytics tools are efficient in storing the data and processing them in real time in order to monitor traffic and make predictions that improve service quality and companies' revenues [3].…”
Section: Big Data In Logistics and Transportation / Primjena Velikih mentioning
confidence: 99%
“…It helps identify traffic problems and make decisions regarding the bus transportation network. As a result, the traffic flow in the city has been improved [3].…”
Section: Big Data In Logistics and Transportation / Primjena Velikih mentioning
confidence: 99%
“…To prevent the above case, we need a document called the document bill of lading (B/L) serves as a receipt that is valid that the cargo has been transported on the vessel, as the agreement carriage between the shipper (sender)/consignee (receiver) with a carrier. The data contained in the B/L document is in accordance with the data sent by the shipper based on the goods that have been put into containers (stuffing) (Ben Ayed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(5) Good communication is not established between company employees. (6) Lack of employee discipline to the rules that have been made by the company (Ben Ayed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%